Investigation of potent anticarcinogenic activity of 1, 3‐diarylpyrazole acrylamide derivatives in vitro. (10th September 2018) - Demiroglu‐Zergeroglu, Asuman; Ayvali, Nurettin; Turhal, Gulseren; Ceylan, Hurmuz; Nacak Baytas, Sultan
Abstract: Objectives: Pyrazole derivatives are pharmacologically powerful agents pointing at new horizons in the development of anticancer therapies. In this study, anticarcinogenic potential of a series of pyrazole‐acrylamide derivatives has been investigated in mesothelial, malignant mesothelioma and lung cancer cell lines. Methods: The effect of compounds on the viability of cells and the distribution of cell cycle were examined through MTS assay and PI staining, respectively. Apoptosis was evaluated via caspase‐3 enzymatic assay and AO/EB staining. Proteins involved in proliferation, survival and apoptosis were analysed by immunoblotting. Key findings: Twelve compounds of 21 ( 4a –4v ) reduced the viability of cells but, only the subset of five ( 4f, 4i, 4j, 4k and 4v) induced the caspase‐3 activity. Among five, only one compound ( 4k ) significantly suppressed phosphorylation and expression of ERK1/2 and AKT proteins in 24 h. Exposing cancer cells to successive concentrations of 4k gave rise to dose‐ and time‐dependent G2/M phase arrest and apoptosis. Conclusions: 4k has revealed its potent antiproliferative activity by decreasing viability and inhibiting proliferation and survival signals of cancer cells. Moreover, 4k has exposed cytostatic and apoptotic effect especially, on cancer cells. Therefore, it may be necessary to examine the biological actions of 4k in vivo as well.